Fundamental Areas of Phenomenology(Including Applications) : Measuring Topological Charges of Optical Vortices with Multi-Singularity Using a Cylindrical Lens. (4th February 2015) - Peng, Yu; Gan, Xue-Tao; Ju, Pei; Wang, Ya-Dong; Zhao, Jian-Lin
Abstract: We present a simple method to measure the topological charges of optical vortices with multiple singularities. Using a cylindrical lens, a vortex beam can decay into a light field distribution with multiple separated dark holes, whose number just equals the topological charge of the input beam. This conclusion is then verified via experiments and numerical simulations of the propagation of vortex beams with multiple singularities. This method is also reliable to measure the topological charges of broadband vortex beams with different distributions of singularities, which does not resort to multiple beam interferometric experiments.